INVESTIGATING THE EFFECTS OF BAMBOO BIOCHAR ON FERTILE SOIL FOR IMPROVING THE PRODUCTION OF Brassica oleraceae - Lestiyani, Ayu; Purnomo, Erry; Widyaningsih, Septy; Fadillah, Khrisna (Agric, 2023)
Cabbage (Brassica oleracea var capitate), broccoli (B. oleraceae L. var italica), carrots, and cauliflower (B. oleracea var botrytis) are the primary vegetable crops grown in Ngablak. The role of chemical fertilizers in crop enhancement cannot be avoided in the production of vegetables. Chemical fertilizers come in a variety of forms, including nitrogenous, phosphate, and potassium fertilizers. Fertilizer use not only boosts crop yield, but also modifies the physical, chemical, and biological aspects of the soil. However, the continual use of chemical fertilizers has led to a loss in soil organic matter (SOM) and a deterioration in the quality of agricultural soil. The excessive use of chemical fertilizers hardens the soil, diminishes soil fertility, pollutes the air, water, and soil, and depletes vital soil nutrients and minerals, consequently posing environmental risks. This research breakthrough is needed to reduce chemical fertilizers. Biochar, a pyrolyzed or anaerobically-grown biomass, could be used. This study examined the effects of biochar on disease suppression and yield in Brassica oleracea plants in rich soils in Magelang, Central Java. The treatment of this study was control, biochar, biochar+compost. The results of this study can be concluded that the maximum wet and dry weight of broccoli and cabbage plants was achieved in the biochar+compost treatment. Biochar and biochar+compost can enhance the nutrient content of the soil in broccoli, cauliflower, and cabbage. In addition, biochar has an effect (positive or negative influence) on disease in test plants. During June observations, the controls had the highest incidence and plant disease severity, whereas adding biochar and biochar+compost reduced disease incidence and plant disease severity. Increased potassium in conjunction with changes in the chemical characteristics i.e. increasing pH, total N, and C- organic of the soil results in the formation of resistance.